Troublesome teeth, search for stones - Enamel-renal syndrome - Soumya Reddy; Niranjana Arumugam; Aparna Iyengar (Wolters Kluwer Medknow Publications, 2023)
Background: Enamel-renal syndrome (ERS), is a rare autosomal recessive disorder involving family with sequence similarity 20 member A (FAM20A) gene. This unique syndrome is characterized by severe enamel hypoplasia, intrapulpal calcification, nephrocalcinosis, or nephrolithiasis. This case report highlights the early presentation and incidental detection of chronic kidney disease (CKD) in a young child with enamel defects. Clinical Description: A 10-year-old girl, with no significant past or family history, presented with delayed tooth eruption and abnormal shaped teeth. She was detected to have generalized gingival hyperplasia and multiple unerupted teeth. Suspecting amelogenesis imperfecta, she was screened for coexisting systemic conditions. On evaluation, abdominal ultrasound demonstrated bilateral nonobstructive nephrolithiasis. Further renal workup done showed an abnormal creatinine (stage 2 CKD) and mild metabolic acidosis. Reduced urinary citrate excretion with no evidence of hypercalciuria was noted on extensive urine assessment. Genetic testing revealed a novel pathogenic variant in FAM20A, confirming the diagnosis of ERS. Management: The child was initiated on citrate supplements, salt restriction, and adequate hydration. She was advised of dental interventions, including pulp therapy and full-coverage restoration of decayed teeth. The family was counseled about the need for close monitoring of growth, renal function, and progression of nephrolithiasis. Conclusion: Prompt screening for renal associations in oro-dental and systemic disease must be undertaken to ensure early detection of kidney disease and timely institution of appropriate treatment. In children diagnosed to have kidney involvement, the importance of regular follow-up with clinical, biochemical, and imaging modalities, even during adulthood, must be emphasized.